2015
DOI: 10.1016/j.atherosclerosis.2015.08.023
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27a decreases the level and efficiency of the LDL receptor and contributes to the dysregulation of cholesterol homeostasis

Abstract: RATIONALE A strong risk factor for atherosclerosis– the leading cause of heart attacks and strokes– is the elevation of low-density lipoprotein cholesterol (LDL-C) in blood. The LDL receptor (LDLR) is the primary pathway for LDL-C removal from circulation, and their levels are increased by statins --the main treatment for high blood LDL-C. However, statins have low efficiency because they also increase PCSK9 which targets LDLR for degradation. Since microRNAs have recently emerged as key regulators of choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 52 publications
(58 reference statements)
1
56
1
8
Order By: Relevance
“…It has only been reported as a target gene of two miRNA (miR-27a and miR-124) [22, 23]. However, relationship between miR-224 and PCSK9 is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has only been reported as a target gene of two miRNA (miR-27a and miR-124) [22, 23]. However, relationship between miR-224 and PCSK9 is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies have identified several miRNAs that negatively regulate LDLR expression, including miR-27a/b, miR-148a, miR-128-1, miR-130b, miR-301b and miR-185. Recently it was shown that miR-27a/b regulate LDLR activity through direct targeting of the LDLR and LDLR adapter protein 1 (LDLRAP1) 57, 80 . Overexpression and inhibition of miR-27b in wild-type mice decreased and increased, hepatic LDLR expression, respectively, however no significant differences were found in circulating LDL-C or total cholesterol 57 .…”
Section: Mirna Regulation Of Ldl Metabolismmentioning
confidence: 99%
“…These data suggested that a therapeutic intervention aimed at decreasing miR-27 might raise hepatic and vascular ABCA1-dependent cholesterol efflux and RCT. The interest in anti-miR-27-based therapies was enhanced by the discovery that miR-27a/b also target directly the low-density lipoprotein receptor (LDLR) and the LDLR-related genes LRP6 and LDLRAP1 [87, 89]. However, no changes in plasma total cholesterol, LDL-c or HDL-c, or in hepatic cholesterol contents were noted in mice overexpressing miR-27 via an adeno-associated virus or following therapeutic silencing with ASOs [87].…”
Section: Mirnas Targeting Hdl Biogenesis and Lipidationmentioning
confidence: 99%